Monastic Architecture of the Circle of Saints Naum and Clement of Ohrid in the Context of the Church Architecture of the First Bulgarian Kingdom and the Architectural Traditions of the Byzantine Provinces of the 9th–11th Centuries - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2020)
The research was prepared with the financial support of Russian Science Foundation, grant no. 20-18-00294, at the Research Institute for Theory and History of Architecture and Town Planning, branch of the Central Research and Project Institute of the Construction Ministry of Russia (Moscow). The article is devoted to the analysis of architectural features of the churches erected by Saints Clement (CA. 835–916) and Naum (CA. 830–910) of Ohrid at the turn of the 9th–10th centuries. The buildings are in an archaeological state, but they are the most important evidence of the development of the architectural tradition of the First Bulgarian Kingdom, which is still one of the most difficult to read pages of medieval architecture in the Balkans. The study of the architectural features of the Ohrid triconch churches of the turn of the 9th–10th centuries allowed us to show their connections with a wide range of monastic architecture of that time. Like other buildings on the lands of the First Bulgarian Kingdom during the time of the baptism and enlightenment of the Bulgarians, these monuments fit in well with the architectural process of the entire region, which was in the state of stagnation in the 9th–10th century, oriented to old patterns. However, there was an attempt to create original solutions in the conditions of the provincial flow of life in these areas, with their still weak links with Constantinople. At the same time, in some areas, such as Adriatic Littoral, the traditions of architecture of previous periods continued. We tried to move away from the study of the monuments on typological grounds, which was typical of Bulgarian researchers. This allowed us to see the complete picture of the development of architectural processes in the First Bulgarian Kingdom, find explanations for some rare typological solutions and stylistic techniques, and more clearly identify the connections between different regions. Thus, in the 9th–10th centuries, there were no separate regional schools in this part of the Balkans, but there were some areas, such as the Adriatic, that quickly emerged from the crisis and actively participated in cultural renewal. The same processes were taking place in the Bulgarian territories as in other regions of the Balkan Peninsula, and just as in other regions, the church architecture here was closely linked to the tasks of Christianization and education of the population.